Penyuluhan Bahaya Rokok Elektrik Menggunakan Animasi 2 Dimensi Iklan Layanan Masyarakat pada Pemuda Desa - Rosanensi, Melati; Sakti, Lanang; Santoso, Heroe; Lestari, Humaediah; Miftahul Madani; Hasbullah (Insan Kreasi Media, 2023)
The aim of this Community Service is to provide education to the public about the dangers of electronic cigarettes which are used as a substitute for conventional cigarettes using 2-dimensional animation of public service advertisements. research methods using: concept, design, material collecting, assembly, testing and distribution. The initial stage that must be carried out is to think about the concept. This stage is used to determine the goal, namely to produce a 2-dimensional animation of public service advertisements on the dangers of electronic cigarettes to make it easier for the community, especially young people in Suntalangu village, to know the dangers of electronic cigarettes, what they are, and who will be the object in This public service advertisement, namely this animation, is aimed at the community, especially youth in Suntalangu village with ages ranging from 13 years to 60 years or passive or active e-cigarette users. Then carry out 2-dimensional animation designs on public service advertisements such as designing images, text, audio, video and animation. then collect materials such as making a 2D animated film in the form of characters, backgrounds, audio files and other supporting materials. After that comes the creation stage, namely editing characters and objects, animating, rendering, dubbing up to the final editing. then testing is carried out to see whether the public service advertisement has been successfully created. And the final stage is distributing or distributing 2-dimensional animations of public service advertisements. The result is that it is hoped that young people will avoid or not use e-cigarettes again.